Multiscale modeling in smart cities: A survey on applications, current trends, and challenges. (March 2022) - Khan, Asif; Aslam, Sheraz; Aurangzeb, Khursheed; Alhussein, Musaed; Javaid, Nadeem
Abstract: A smart city model views the city as a complex adaptive system consisting of services, resources, and citizens that learn through interaction and change in both the spatial and temporal domains. The characteristics of dynamic evolution and complexity are key issues for megacity planners and require a new systematic and modeling approach. Multiscale models involved in smart cities and megacities have recently become a popular topic because they can understand complex adaptive systems and efficiently solve complex problems at multiple scales (i.e., micro, meso, and macro) to improve system efficiency and reduce computational complexity and cost. However, there are numerous opportunities to improve this interdisciplinary field considering the lack of applicability of the multiscale modeling approach in megacities and smart cities, and the potential of multiscale modeling in various complex systems within smart cities. Therefore, a review that summarizes the state-of-art researches and opens opportunities around the theme of multiscale modeling participating in megacities and smart cities is warranted. This study, therefore, provides a comprehensive review covering the introduction of megacities, their current challenges, and their emergence in smart cities. Then, the introduction of the smart city along with its characteristics and different generations is disclosed. Moreover, we shed light on multiscale modeling, its categories (i.e., sequential multiscale modeling and concurrent multiscale modeling), and the need for multiscale modeling in megacities and smart cities along with its emerging applications. Finally, based on a literature review, the study highlights the current challenges and future directions related to multiscale modeling in megacities and smart cities, which provide a roadmap for the optimized operation of megacities and smart city systems. Highlights: This paper provides a systematic review of megacities (MCs), and smart cities (SCs). Further, it also sheds light on the transformation of MCs into SCs. A comprehensive literature review of multiscale modeling (MM) in Mcs and SCs is provided. We also highlight emerging applications of MM in MGs and SCs. Finally, the study provides research challenges related to MM in MCs and SCs.